Educational Inequality In Indonesia - I Made Suartana; Gede Raharja Dangin; I Gede Kusuma Wahyudi; Basilius Redan Werang (International Journal of Education, Vocational and Social Science, 2025)
Education plays a crucial role in advancing the nation and improving the quality of human resources in Indonesia. However, the education gap remains a major issue that needs to be addressed immediately, both in terms of access, quality, and outcomes. This article examines various forms of education gaps, such as differences in access between urban and rural areas, obstacles to access to education for women, disparities in education quality between elite private and public schools, and variations in learning outcomes as reflected in student participation and achievement levels. This research uses a literature review method, analyzing recent sources from the past ten years to identify the causes, challenges, and solutions. The study reveals that the gap is caused by socioeconomic, geographic, and cultural factors, as well as imbalances in policies and resources. Therefore, addressing the education gap requires a comprehensive approach, encompassing quality improvement in disadvantaged areas, equitable access to technology, teacher training, and the implementation of fair and inclusive policies. It is hoped that these efforts will create quality education and equal opportunities for all Indonesian children, regardless of social or geographic background.